DRTA (DIRECT READING THINKING ACTIVITY) STRATEGY IN IMPROVING READING COMPREHENSION ABILITY AT MAN 1 KOTA PROBOLINGGO - Briliana, Fany Filosofia; Thamrin, Moh Husni (English Edu: Journal of English Teaching and Learning, 2024)
This study aims to discuss the reading comprehension ability of students in class XI Mipa 1 at MAN 1 Kota Probolinggo. This research uses CAR (classroom action research). The sample in this study were all students of class XI Mipa 1 who were housed in MAN 1 Kota Probolinggo. The data collection technique in this study used google forms and tests in the form of sheets of paper containing the subject matter. In accordance with the problem that is the focus of this research, namely a descriptive description of the implementation of the DRTA method to improve reading comprehension in class XI Mipa 1 Students at MAN 1 Kota Probolinggo, the researchers used a CAR by describing the data that the researchers obtained as a result of a study. This study states that the DRTA method applied by the researcher has very satisfactory results, with all 22 students in class XI Mipa 1 ending experiencing complete reading comprehension.